Ex Libris [Zbigniewa Dolatowskiego] [Zbigniew Dolatowski]. - Dolatowski, Zbigniew (1927-2001) (1971)
Przedstawia dużą sygn. aut. pośrodku, niżej napis: Ex Libris. Pod wyobrażeniem autograf aut. i data.